2020
DOI: 10.1007/s00198-020-05619-2
|View full text |Cite
|
Sign up to set email alerts
|

Sleep duration and bone health measures in older men

Abstract: The associations between objective measures of sleep duration and bone outcomes in older men are unknown. No consistent, significant association was identified between sleep duration and bone mineral density (BMD) in the current analysis. However, future research should determine if vitamin D status modifies this relationship. Introduction Prior studies, predominantly in women, reported that long and short self-reported sleep duration are associated with lower BMD. Associations between actigraphy-determined sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 46 publications
3
12
1
Order By: Relevance
“…A recent cross-sectional study of >11,000 postmenopausal women showed that those reporting a short sleep time (£5 hours of sleep) had lower BMD and more osteoporosis in the hip and other body parts than those in the reference group ( ‡7 hours of sleep) after adjusting for covariates 46 . However, recent longitudinal and cross-sectional studies did not confirm this association 47,48 . Insomnia and OSA could affect BMD 10,49 .…”
Section: Sleep Medication As a Risk For Falls And Mvasmentioning
confidence: 90%
“…A recent cross-sectional study of >11,000 postmenopausal women showed that those reporting a short sleep time (£5 hours of sleep) had lower BMD and more osteoporosis in the hip and other body parts than those in the reference group ( ‡7 hours of sleep) after adjusting for covariates 46 . However, recent longitudinal and cross-sectional studies did not confirm this association 47,48 . Insomnia and OSA could affect BMD 10,49 .…”
Section: Sleep Medication As a Risk For Falls And Mvasmentioning
confidence: 90%
“…Some previous studies demonstrated that unhealthy sleep duration was associated with decreased BMD or increased risk of osteoporosis [9,10,[30][31][32]. For example, Ochs-Balcom et al observed that women with short sleep duration (≤ 5 h/per night) showed lower BMD and higher risk of low bone mass and osteoporosis than individuals with a 7-h sleep duration [30].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al found that post-menopausal women with long sleep duration (> 10 h/day) showed a higher risk of osteoporosis than those with normal sleep duration (8–9 h/day) [ 8 ]. However, it should be noted that there is still no reliable conclusion because some studies found that long or short sleep durations might not contribute to decreased BMD [ 9 , 10 ]. For example, Swanson et al observed that nocturnal sleep duration was not independently associated with hip BMD among postmenopausal women irrespective of the method of assessment of sleep duration (objective or subjective) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent publications on the relationship between sleep duration and BMD were the first to use wrist actigraphy instead of self-report on questionnaire to establish sleep duration. The association between BMD and objectively measured sleep duration was evaluated using the Osteoporotic Fractures in Men (MrOS) Study and the SOF cohorts [67,68 ▪ ]. Although no significant association was identified between objectively determined nighttime sleep duration and BMD in either cohort, these articles did raise two potential considerations for future research [67,68 ▪ ].…”
Section: Bone Health Is Associated With Abnormal Sleep Durationmentioning
confidence: 99%